Analisis Kriminologis terhadap Penyebaran Konten Pornografi LGBT di Dunia Maya (Studi Putusan Pengadilan Nomor: 343/Pid.Sus/2020/Pn.Pbr) - Yaswirman Yaswirman; Nilma Suryani; Vivi Dwi Yulian Benni (LPPM Universitas Ekasakti Padang, 2023)
In essence, social media gave birth to new concerns, including the emergence of the development of the spread of pornography with pornographic sites in sharing various types of site views which are very tempting and have a major influence on the nation's morals and personality which will have a negative impact on Indonesia so that it threatens life and social order. Indonesian society. The development of pornography in society has also resulted in an increase in immoral acts. Related to the Internet and communication tools, of course very closely related to Cybercrime (Crime in cyberspace). According to the Organization of European Community Development (OECD) Cybercrime is all forms of illegal access to a data transmission. That is, all types of illegal activity in a computer system is a crime. In this thesis entitled